The effects of religiosity on earnings management under obedience pressure - Mahmudi Mahmudi; Supriyadi Supriyadi (Journal of Economics, Business, and Accountancy Ventura, 2019)
This paper examined the effect of obedience pressure on real earnings management. It also also investigated whether the relationship between obedience pressure and real earnings management is moderated by individual’s religiosity level. Religiosity is an individual believed as sources of ethical value that would normatively affect the management ethical decision. Prior studies have documented that management decision could be influenced by obedience pressure, however, there is limited study that specifically tested the effects of obedience pressure and religiosity on real earnings management. This study utilized a laboratory experiment with a 2 x 2 (obedience pressure x level of religiosity) factorial design involving 89 participants. This study found that individuals under obedience pressure were more likely to perform real earnings management than control group. However, religiosity did not significantly mitigate the association between obedience pressure and real earnings management. There is no significant effect of individual’s religiosity level on real earnings management decision.